SOME NOTES ON TRE BROAD-LEAVED EVERGREEN FORESTS ON THE AZORES - KLOTZLI, F. (Annali di Botanica, 2003)
<img title="klotzli_et_al._pagg._125-151_512" src="http://ojs.uniroma1.it//public/site/images/francesco_spada/klotzli_et_al._pagg._125-151_512.jpg" alt="klotzli_et_al._pagg._125-151_512" width="512" height="425" />